2015
DOI: 10.1002/jemt.22503
|View full text |Cite
|
Sign up to set email alerts
|

Geometric complexity identifies platelet activation in familial hypercholesterolemic patients

Abstract: Familial hypercholesterolemia (FH), a genetic disease, is associated with a severe incidence of athero-thrombotic events, related, also, to platelet hyperreactivity. A plethora of methods have been proposed to identify those activated circulating platelets, none of these has proved really effective. We need efficient methods to identify the circulating platelet status in order to follow the patients after therapeutic procedures. We propose the use of computerized fractal analysis for an objective characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…We have shown that parameters characterising the platelet shape allow for the sensitive characterisation of different activation states of platelets. This research is supported by the findings of Bianciardi and coworkers who have shown that platelets activated with thrombin [15] as well as platelets from diabetic patients [14] and from patients with primary hypercholesterolemia [13] showed significant differences in the fractal dimension of their outlines on electron microscopic images. Furthermore Canault et al [28] found on fluorescence microscopic images that platelets from RASGRP2 knockout mice show a significantly reduced formation of filopodia during spreading on fibrinogen as compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have shown that parameters characterising the platelet shape allow for the sensitive characterisation of different activation states of platelets. This research is supported by the findings of Bianciardi and coworkers who have shown that platelets activated with thrombin [15] as well as platelets from diabetic patients [14] and from patients with primary hypercholesterolemia [13] showed significant differences in the fractal dimension of their outlines on electron microscopic images. Furthermore Canault et al [28] found on fluorescence microscopic images that platelets from RASGRP2 knockout mice show a significantly reduced formation of filopodia during spreading on fibrinogen as compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 82%
“…PSC can be quantitatively described by applying different geometrical descriptors to the platelet outline (PO) [12]. It has been found that the PO of platelets imaged by high-resolution darkfield microscopy [12] and electron microscopy [13][14][15][16] shows fractal behaviour and therefore can be described using the language of fractal geometry. Fractal geometry has gained increasing interest in life sciences as it enables a simple numerical description of complex and irregular forms [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%